A facile method for grafting functional hydrogel films on PTFE, PVDF, and TPX polymers. Issue 22 (27th May 2022) - Fischer, Thorsten; Tenbusch, Jan; Möller, Martin; Singh, Smriti
Abstract : In this work we show a simple, one step process of grafting highly hydrophilic hydrogel layer on chemically inert polymers. This applied method has a potential to form the basis for advanced biocompatible and biofunctional surface engineering. Abstract : The use of polymeric materials in biomedical applications requires a judicious control of surface properties as they are directly related to cellular interactions and biocompatibility. The most desired chemical surface properties include hydrophilicity and the presence of functional groups for surface modification. In this work, we describe a method to graft a highly stable, ultra-thin, amine-functional hydrogel layer onto highly inert surfaces of poly(tetrafluoroethylene) (PTFE), poly(vinylidene fluoride) (PVDF), and poly(4-methyl-1-pentene) (PMP or TPX). Covalent grafting is realized with hydrophilic poly(vinylamine- co -acetamide)s by C–H insertion crosslinking (CHic) chemistry initiated by UV light. These polyvinylamides carry tetrafluorophenyl azide groups as photo or thermo activated binding sites and contain further free amine groups, which can be used to bind peptides such as biological ligands, polysaccharides, or other hydrogel layers. The covalently bound surface layers resist intensive Soxhlet extraction confirming the stability of the coating. Fluorescent staining verified the accessibility of free primary amine groups, which can be used for the functionalization of the surface with bioactive molecules. The coating demonstrates hydrophobic wetting behavior when conditioned in air and hydrophilic wetting behavior when conditioned in water showing the presence of loosely crosslinked polymer chains that can re-orient. We believe that the reported application of CHic for the surface modification of fluorinated polymers like PTFE and PVDF as well as TPX can form the basis for advanced biocompatible and biofunctional surface engineering.